Development Of A Portable Ablution System For Muslims From Ergonomics Approach - Mukhtar, Mohd Fariduddin; Hasim, Nur Aiman Hanis; Rosley, Mohd Idain Fahmy; Hussin, Mohamed Saiful Firdaus; Muhamad Damanhuri, Amir Abdullah; Samsudin, Adam (Asian Research Publishing Network, 2021)
Ablution is Muslim’s act of washing oneself before performing prayers. This ritual only involves several parts of the body. However, during this process, water was wasted too much which interchanging between body parts even though Islam urges Muslim to reduce water usage during ablution. Other than that, the newly developed design will check for its ergonomic since comfortability and safety are essential for establishing a product. Hence so, this research is proposing a new design of an ablution system. This ablution system designed as a portable and user-friendly system for all ages to be used. The design for this ablution system does consider the ergonomics of human position. It also proposes a way to conserve the wasted water from ablution process. Design is made from the suggestions from RULA analysis by CATIA V5. This analysis proposed a better angle for better measurement of the proposed design. Finally, the study concluded with limitations and future research directions.